2015
DOI: 10.1155/2015/823136
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Quality of Attention and Cognitive Competence with Motor Action in Stroke Patients

Abstract: It is considered that cognitive function and attention could affect walking, motion control, and proper conduct during the walk. To determine whether there is a difference in the quality of attention and cognitive ability in stroke patients and patients without neurological damage of similar age and education and to determine whether the connection of attention and cognition affects motor skills, the sample consisted of 50 stroke patients tested with hemiparesis, involved in the process of rehabilitation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 8 publications
0
7
1
2
Order By: Relevance
“…A possible reason for the different effects of motor imagery is the decline of cognitive function after a patient experiences a stroke. A previous study reported that not only motor function but also cognitive function declines after a stroke [31]. Moreover, cognitive function is largely associated with the ability to execute motor imagery [32].…”
Section: Clinical Studies Of Motor Imagerymentioning
confidence: 98%
See 1 more Smart Citation
“…A possible reason for the different effects of motor imagery is the decline of cognitive function after a patient experiences a stroke. A previous study reported that not only motor function but also cognitive function declines after a stroke [31]. Moreover, cognitive function is largely associated with the ability to execute motor imagery [32].…”
Section: Clinical Studies Of Motor Imagerymentioning
confidence: 98%
“…The cognitive function is greatly associated with cognitive information processing. Therefore, the level of difficulty is higher in motor imagery than action observation, especially for stroke patients who see a decline in cognitive function [31]. How then are action observation and motor imagery used for physical therapy?…”
Section: Application Of Motor Imagery and Action Observation To Physimentioning
confidence: 99%
“…A well-known example of this is motor neglect ( 2 ), in which unilateral motor dysfunction arises from a lateralized attentional bias, rather than because of primary motor, or corticospinal tract, disruption. However, focal brain lesions also impair nonspatial forms of attention, such as alertness ( 1 ), that are associated with motor function ( 3 , 4 ) although the nature of this relationship is unclear.…”
mentioning
confidence: 99%
“…В результате аппаратных специ-ализированных функциональных тренировок и БОС-тренировок бытовой направленности (task specifi c training) больные адаптируются к выполне-нию бытовых навыков вне занятий (питание, туа-лет, уход за собой, профессиональные навыки) [4,[16][17][18][19][20][21]. Одновременно с этим виртуальный и игро-вой характер тренировок активизирует когнитив-ные и эмоциональные процессы в головном мозге, за счет которых поддерживается устойчивое внима-ние больного в ходе одного занятия и сохраняется высокая мотивация на протяжении всего курса ле-чения [5,8,14,[22][23][24].…”
Section: ключевые слова: инсульт верхняя конечность реабилитация рunclassified